FACTORS AFFECTING ECONOMIC GROWTH IN THE BANGKA BELITUNG ISLANDS; ANALYSIS OF HUMAN ROLES AND THEIR PARTICIPATION - Sapitri, Rima; Mentari, Rahmi; Abadiyah, Fajriyatul (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2026)
This study aims to analyze the effect of the Human Development Index (HDI) and Labor Force Participation Rate (LFPR) on economic growth in Bangka Belitung Islands Province for the period 2020–2025. A quantitative approach using a multiple linear regression model based on panel data was employed, with model selection carried out through Chow, Hausman, and Lagrange Multiplier tests, which resulted in the Random Effect Model (REM) as the most appropriate model. Secondary data were obtained from official publications of the Central Statistics Agency (BPS) and relevant scientific sources. Partial test results indicate that HDI has a positive and significant effect on economic growth with a coefficient of 1.873 (p-value = 0.002), meaning that every 1-point increase in HDI will increase economic growth by 1.873 percent. LFPR also has a positive and significant effect with a coefficient of 0.645 (p-value = 0.029), where every 1 percent increase in LFPR will increase economic growth by 0.645 percent. Simultaneously, HDI and LFPR together have a significant effect on economic growth with an F-statistic value of 17.303 (p-value = 0.0012) and are able to explain 87.42% of the variation in economic growth (R² = 0.8742). These findings imply that improving human resource quality and expanding labor force participation are key factors in driving inclusive and sustainable regional economic growth in Bangka Belitung Islands Province.